SISTEM PENDUKUNG KEPUTUSAN KELULUSAN PELATIHAN KERJA MENGGUNAKAN METODE FUZZY - Nur Sucahyo; Lela Nurlaela (Institut Teknologi dan Bisnis Swadharma, 2021)
Human resources are an important requirement for companies, both large and small companies. Procurement of manpower is a process that needs to be optimized to obtain competent human resources capable of encouraging the achievement of organizational goals optimally. The selection of prospective workers becomes a difficult thing to decide if the number of applicants is quite large with diverse backgrounds and the criteria determined by the organization are quite complex. This study aims to produce a decision support system in terms of determining prospective applicants who pass the job training period held by PT. Resqtec Indonesia. The method used is field research using interview and observation techniques in analyzing the needs and problems of current conditions and producing proposed system designs to be developed. The results of the research are in the form of a prototype decision support system using fuzzy logic with criteria for work productivity, work quality, and work discipline with the output in the form of recommendations that are not recommended, considered, and recommended.